Internalisasi Nilai-Nilai Pancasila Dalam Proyek Konstruksi Yang Beretika - Anugrah Haryata Pratama (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
Pancasila is a reflection of the habits and customs that have been alive in society even before the establishment of the Indonesian nation de jure and de facto, Pancasila has been alive from habits and grown in customs that are still believed by society until now. i. Type of research The type of research in this study is normative juridical. ii. Research specifications The research specifications used in this study are analytical descriptive research. Ethics is a subfield of philosophy related to the systematic study, defense, and support of normative behavioral theory. The negative impact of globalization has shifted the cultural customs of society so that they are far from empathy, ethics, and the basic values ​​contained in Pancasila. The obstacle is the politics of gratitude, in political contestation is still very close.